Line space gathering for single scattering in large scenes - Xin, Sun; Lin, Steve; Guo, Baining (2011)
A light gathering process may reduce the computational resources and storage required to render a scene with a participating homogeneous media. According to some implementations, Efficiency may be obtained by evaluating the final radiance along a viewing ray directly from the lighting rays passing near to it, and by rapidly identifying such lighting rays in the scene. To facilitate a search for nearby lighting rays, the lighting rays and viewing rays may be represented as a 6D point and a plane according to the corresponding Plucker coordinates and coefficients, respectively.
US Patent 8922556 B2